A novel high-weather-resistant resin coating and a preparation method thereof
Patent Information
- Application Number
- CN202611020938.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]针对现有防腐环氧树脂涂料微裂纹无自修复功能、强腐蚀环境阻隔效率低、低温抗冲击性差的不足,本发明提供了一种高耐候新型树脂涂料及其制备方法
本发明通过在涂料体系中引入壁材为改性三聚氰胺甲醛树脂、内部包覆缓蚀型修复剂的定向释放自修复微胶囊,同时调控微胶囊壁材的弹性模量与涂料生产阶段高速分散工序的剪切力适配,实现微胶囊生产存储阶段不提前破损、涂层出现微裂纹时定向破裂释放修复剂的效果,有效解决了现有技术中涂层无自修复功能、传统自修复微胶囊易在制备过程中提前失效的缺陷。释放的修复剂不仅可物理填补微裂纹,还可在损伤处形成钝化保护层,阻断腐蚀介质的渗透路径。
Smart Images

Figure CN122917629A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high weather-resistant resin coating technology, and in particular to a novel high weather-resistant resin coating and its preparation method. Background Technology
[0002] High weather-resistant and anti-corrosion resin coatings are widely used in heavy-duty fields such as marine engineering equipment, outdoor power transmission and transformation facilities, and chemical storage tank corrosion protection. As downstream industries continue to increase their requirements for the service life and adaptability of protective coatings to complex environments, existing coatings must simultaneously meet multiple performance requirements such as resistance to ultraviolet aging, resistance to strong acid and alkali corrosion, impact resistance, and micro-damage self-repair. This is currently the focus of research and development in the field of anti-corrosion coatings.
[0003] Chinese patent application number 202510162223.6 discloses a high weather-resistant and anti-corrosion epoxy resin coating. The technical solution involves introducing a difluorene structure and grafted modified glass flakes into the epoxy resin molecular chain, and combining it with modified polysulfide rubber with introduced POSS groups as a toughening component to prepare the coating. This solves the problems of poor temperature resistance and insufficient resistance to damp heat in traditional epoxy coatings. However, it does not solve the problem of self-repair of microcracks in the coating. The micro-damage generated during the service of the coating cannot be automatically repaired, and corrosive media can easily penetrate rapidly along the damage path. At the same time, in this solution, the glass flakes are only grafted to the resin main chain through chemical bonds. After film formation, the flakes have poor orientation and the barrier efficiency decreases significantly under strong acid and alkali corrosion environments. Moreover, the crosslinking density of the system is too high after curing. The impact resistance of the coating is significantly reduced in low-temperature environments below -20℃, and it is prone to brittle cracking and peeling.
[0004] Another mainstream technology currently is functional epoxy coatings with added urea-formaldehyde self-healing microcapsules. This type of coating incorporates a liquid repair agent encapsulated within microcapsules and mixed into the coating system. When microcracks appear in the coating, the microcapsules rupture, releasing the repair agent to fill the cracks, thus exhibiting a certain degree of self-repair capability. However, the microcapsule wall materials used in this technology have poor strength adaptability, and the high-speed dispersion process during coating preparation can easily cause premature rupture and failure of the microcapsules. The repair agent only provides physical filling and lacks simultaneous corrosion inhibition and passivation effects. Furthermore, the strong acid and alkali barrier properties of the film-forming resin have not been optimized, making it difficult to adapt to the usage requirements of highly corrosive environments such as chemical storage tanks.
[0005] In response to the shortcomings of existing anti-corrosion coatings, such as the lack of self-healing function for microcracks, low efficiency in blocking strong acids and alkalis, poor low-temperature impact resistance, and premature damage to self-healing microcapsules, there is an urgent need to develop high-performance weather-resistant resin coatings that can adapt to multiple complex working conditions and meet the protection needs of downstream industries for long service cycles. Summary of the Invention
[0006] To address the shortcomings of existing anti-corrosion epoxy resin coatings, such as lack of self-healing function for microcracks, low barrier efficiency in highly corrosive environments, and poor low-temperature impact resistance, this invention provides a novel high-weather-resistant resin coating and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A novel high-weather-resistant resin coating comprises the following raw materials in parts by weight: 45-55 parts of rare earth-doped modified epoxy resin serve as the main film-forming material, combining rare earth passivation and corrosion inhibition with the physical barrier effect of glass flakes; 20-28 parts of fluorine-modified hydroxyl acrylic resin synergistically improve the coating's UV aging resistance and surface hydrophobicity and antifouling properties; 25-32 parts of amino resin serve as a crosslinking agent to ensure that the crosslinking density meets requirements after system curing; 8-12 parts of fluorine-containing side-chain modified polysulfide rubber toughens the system while further improving the coating's water and weather resistance; 5-8 parts of corrosion-inhibiting self-healing microcapsules can automatically release repair agents and corrosion inhibitors when microcracks occur in the coating, extending the coating's service life; 7-10 parts of titanium dioxide; 2-4 parts of hydrophobic modified fumed silica; 0.4-1.0 parts of dispersant; 0.5-0.8 parts of leveling agent; 0.2-0.4 parts of defoamer; 0.7-1.0 parts of drier; and 12-20 parts of solvent.
[0008] Preferably, the dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is cobalt isooctanoate, and the solvent is a mixture of propylene glycol methyl ether acetate and ethyl acetate in a volume ratio of 1:1. All the selected additives have excellent compatibility with the film-forming system.
[0009] Preferably, the preparation of the rare earth-doped modified epoxy resin includes the following steps: S1. 1,10-Phenanthroline-2-carboxylic acid methyl ester and selenium dioxide were added to glacial acetic acid solvent, and the mixture was heated to 110-115℃ and stirred under reflux for 6-7 hours. Selenium dioxide was used to selectively oxidize the active hydrogen at the 9-position to avoid over-oxidation and the generation of byproducts. After removing the solvent by rotary evaporation under reduced pressure, the intermediate 9-keto-1,10-phenanthroline-2-carboxylic acid methyl ester with a purity of over 98% was obtained by recrystallization with ethyl acetate. S2. Add cerium-doped glass flakes to a 95% (v / v) ethanol aqueous solution and stir for 15-20 min. Add an ethanol solution of KH550 silane coupling agent and reflux at 80-85℃ for 4-4.5 h. After filtration, wash three times each with deionized water and ethanol and dry to obtain amino-modified cerium-doped glass flakes. Cerium element forms a passivation film on the substrate surface, which, together with the layered barrier effect of glass flakes, blocks the penetration path of corrosive media. S3. The intermediate methyl 9-keto-1,10-phenanthroline-2-carboxylic acid was added to a sodium hydroxide methanol solution and refluxed for 2 hours. The pH was adjusted to acidic to precipitate a solid. After drying, the solid was added to dichloromethane, and the carbodiimide condensing agent EDC and catalyst DMAP were added. The mixture was stirred and activated for 30 minutes. Then, amino-modified cerium-doped glass flakes were added. The mixture was stirred at room temperature for 24 hours under nitrogen protection. Grafting was achieved by amidation. The reaction conversion rate could reach more than 85%, with no excess by-product residue. The mixture was filtered and washed to obtain amide-grafted 9-keto-diazonium-modified glass flakes. S4. Add 9-keto-diazonium fluorene-modified glass flakes, phenol, and zinc chloride to concentrated hydrochloric acid, heat to 45-50℃ and stir for 12-13 hours. The 9-keto group undergoes an electrophilic addition reaction with two molecules of phenol to obtain a bisphenol-terminated modified glass flake intermediate. Under nitrogen protection, mix bisphenol A, the bisphenol-terminated modified glass flake intermediate, epichlorohydrin, and tetrabutylammonium bromide, heat to 75-80℃ and stir for 3.5-4 hours. Add a 40%-45% sodium hydroxide solution and continue the reaction for 1-1.5 hours. After extraction, washing, drying, and vacuum distillation, obtain rare earth-doped modified epoxy resin. This process can simultaneously introduce the rigid structure of diazonium fluorene, rare earth corrosion inhibitors, and glass flake barrier components into the epoxy resin backbone, improving the coating's heat resistance, mechanical strength, and corrosion resistance.
[0010] Preferably, in step S2, the cerium doping mass fraction of the cerium-doped glass flakes is 2%-3%, maximizing the passivation and corrosion inhibition effect of rare earth ions while ensuring the physical barrier properties of the glass flakes; the concentration of the ethanol solution of the silane coupling agent is 0.12-0.16 mol / L, and the ratio of cerium-doped glass flakes, ethanol aqueous solution, and silane coupling agent ethanol solution is 5-6 g: 50-60 mL: 720-760 mL; in step S4, the ratio of bisphenol A, bisphenol end-modified glass flake intermediate, and epichlorohydrin is 22-24 g: 4-4.2 g: 190-195 g, so that the epoxy value of the finally synthesized epoxy resin is stable at 0.42-0.48 eq / 100 g, and the crosslinking density after curing is suitable, balancing hardness and toughness.
[0011] Preferably, the preparation of the fluorinated side-chain modified polysulfide rubber includes the following steps: S1. Mix terminal thiol liquid polysulfide rubber with 1,2-dichloroethane and stir evenly. Add 0.5 mol / L sodium ethoxide ethanol solution dropwise. Use strong alkali to fully activate the terminal thiol groups. Heat to 55-60℃ and stir for 3-3.5 h. The reaction conversion rate can reach more than 92%. Remove the solvent and excess reactants by vacuum distillation to obtain terminal chlorinated polysulfide rubber. S2. Under a nitrogen protective atmosphere, add the terminal chlorine polysulfide rubber to a mixed solvent obtained by mixing isopropanol and toluene at a volume ratio of 2:1. After stirring for 10-15 min, add N-allyl perfluorooctyl sulfonamide, heat to 75-80℃ and stir for 4.5-5 h. After cooling, filter to remove the generated sodium chloride salt, and distill under reduced pressure to obtain terminal alkenyl polysulfide rubber containing perfluorinated side chains. The perfluorinated side chains can migrate to the coating surface during film formation, increasing the water contact angle of the coating surface to over 110°, and significantly improving water resistance and weather resistance. S3. Add the terminal alkenyl polysulfide rubber containing perfluorinated side chains to dichloromethane and stir for 30-35 min. Add m-chloroperoxybenzoic acid and stir at room temperature for 8-9 h to oxidize the double bonds and obtain the fluorinated epoxy intermediate. S4. Add the fluorinated epoxy intermediate and aminopropylheptyl POSS to dimethyl sulfoxide, heat to 50-60℃ and stir for 24-25 hours. The epoxy ring-opening grafted POSS structure can improve the heat resistance stability of polysulfide rubber and prevent the coating from softening and falling off at high temperature. Filter and dry to obtain fluorinated side chain modified polysulfide rubber.
[0012] Preferably, in step S2, the ratio of terminal chlorinated polysulfide rubber to N-allyl perfluorooctyl sulfonamide is 1 mol: 1.05 mol, which ensures complete reaction of the terminal chlorine and avoids excessive fluorinated monomer residue affecting coating adhesion; in step S4, the ratio of fluorinated epoxy intermediate to aminopropylheptyl POSS is 8-9 g: 19-21 g, which ensures uniform grafting of POSS and prevents agglomeration that affects system compatibility.
[0013] Preferably, the wall material of the corrosion-inhibiting self-healing microcapsules is melamine-formaldehyde resin with a thickness of 1.2-1.5 μm, which ensures that the microcapsules will not break prematurely during normal storage and preparation, and can also break and release the core material in time when microcracks occur in the coating. The core material is a mixture of linseed oil and benzotriazole at a mass ratio of 7:3, which has the dual functions of crack filling and corrosion inhibition and passivation. The microcapsules have a particle size of 15-25 μm, a shear strength of not less than 3000 rpm, and a temperature resistance of not less than 120℃, which is suitable for the coating preparation process requirements and will not fail prematurely.
[0014] Preferably, the preparation steps of the corrosion-inhibiting self-healing microcapsules are as follows: melamine and a 37% formaldehyde solution are mixed at a mass ratio of 1:2, the pH is adjusted to 8-9, and the mixture is heated to 60-65℃ and stirred until the solution is clear to obtain a melamine-formaldehyde prepolymer; the core material is added to a 2% sodium dodecylbenzenesulfonate aqueous solution and emulsified at high speed for 20-25 minutes to obtain a core material emulsion; the prepolymer is slowly added dropwise to the core material emulsion, with a prepolymer to core material mass ratio of 1:2, which can ensure that the core material content of the microcapsules can reach more than 65%, resulting in excellent self-healing efficiency; the pH is adjusted to 4-5, and the mixture is heated to 70-75℃ and stirred for 3-3.5 hours; after cooling, the mixture is filtered, washed, and dried to obtain the corrosion-inhibiting self-healing microcapsules.
[0015] Preferably, the steps include: S1. Rare earth-doped modified epoxy resin, fluorinated side-chain modified polysulfide rubber, and fluorinated modified hydroxyl acrylic resin are stirred and mixed at 85-95℃ for 2-2.5h, and amino resin is added and stirred at 65-75℃ for 1-1.5h to obtain the base material. S2. Add titanium dioxide and hydrophobically modified fumed silica to the base material and disperse at high speed of 2800-3000 r / min for 20-25 min to initially break up pigment and filler agglomerates. Then add dispersant, leveling agent, defoamer, drier and solvent. Disperse ultrasonically at 300-400W power for 15-20 min to ensure uniform dispersion of pigments and fillers and avoid defects such as pinholes and decreased mechanical properties. Cool down to 40-50℃. S3. Add the corrosion-inhibiting self-healing microcapsules to the dispersed material and stir at a low speed of 800-1000 r / min for 10-15 min to prevent the microcapsules from breaking prematurely due to high shear or high temperature, and to ensure that the self-healing function is stable and effective, thus obtaining a new type of high weather-resistant resin coating.
[0016] Preferably, in step S2, the high-speed dispersion speed does not exceed 3000 rpm, which matches the shear strength of the microcapsules and avoids premature rupture; in step S3, the stirring temperature is controlled at 40-50℃, which ensures the fluidity of the system and does not cause the low-boiling-point additives to volatilize and become ineffective.
[0017] The present invention has the following beneficial effects: This invention introduces directionally released self-healing microcapsules, with modified melamine-formaldehyde resin as the wall material and internally encapsulated with a corrosion-inhibiting repair agent, into the coating system. Simultaneously, the elastic modulus of the microcapsule wall material is adjusted to match the shear force of the high-speed dispersion process during coating production. This achieves the effect of preventing premature breakage of the microcapsules during production and storage, and directional rupture to release the repair agent when microcracks appear in the coating. This effectively solves the defects of existing technologies, such as the lack of self-healing function in the coating and the premature failure of traditional self-healing microcapsules during preparation. The released repair agent not only physically fills the microcracks but also forms a passivation protective layer at the damaged site, blocking the penetration path of corrosive media.
[0018] This invention modifies glass flakes through a double-layer interface, further loading orientation guiding groups on the basis of silane coupling agent grafting. During film formation, the flakes can be oriented along the horizontal direction of the coating, and at the same time form a multi-level barrier network with the difluorene structure of the modified epoxy resin backbone, extending the penetration path of strong acid and alkali corrosive media, improving corrosion barrier efficiency, and effectively solving the problems of disordered glass flake arrangement and rapid decay of protective performance under strong corrosive environment in the prior art.
[0019] This invention, by combining a small amount of terminal hydroxyl fluoroether flexible segments with POSS groups grafted onto modified polysulfide rubber, retains the high-temperature weather resistance of the original system while lowering the glass transition temperature of the system, improving the impact resistance of the coating in low-temperature environments, and avoiding the problem of brittle cracking and peeling. It solves the defects of insufficient low-temperature toughness and poor adaptability to low-temperature conditions caused by excessively high crosslinking density in the prior art.
[0020] The coating of this invention can be directly adapted to conventional construction processes such as spraying, roller coating, and brushing of existing epoxy coatings without the need for additional special construction equipment. It can be widely used in anti-corrosion protection scenarios with multiple complex working conditions, such as marine engineering equipment, coastal power transmission and transformation facilities, chemical acid and alkali storage tanks, and cold-region outdoor equipment. Compared with existing similar anti-corrosion coatings, its service life is significantly improved, and it has high industry promotion value. Attached Figure Description
[0021] Figure 1 This invention provides a flowchart of a method for preparing a novel high-weather-resistant resin coating; Figure 2 This is a bar chart comparing the core performance of each group of samples proposed in this invention; Figure 3 This is a line graph showing the change in the penetration depth of the corrosive medium as a function of immersion time, as proposed in this invention. Figure 4 This is a bar chart comparing the microcapsule breakage rate under different dispersion speeds proposed in this invention. Detailed Implementation
[0022] The following will refer to the appendices in the embodiments of the present invention. Figure 1-4The technical solutions in the embodiments of the present invention are clearly and completely described herein. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0023] Explanation of core technical features The modified epoxy resin was prepared by reacting bisphenol A epoxy resin E-51 with 9,9-bis(4-aminophenyl)fluorene at a mass ratio of 7:3 under nitrogen protection at 160℃ for 4 hours. The introduction of diazofluorene structure into the main chain improves corrosion resistance and forms a multi-level barrier network in synergy with the double-layer modified glass flakes. The double-layer modified glass flakes were grafted with amino active groups and long alkyl oriented groups in two steps, with the grafting rate controlled at 2%-4%. During film formation, the flakes were oriented along the horizontal direction of the coating to extend the penetration path of corrosive media. The self-healing microcapsules use organosilicon-modified melamine-formaldehyde as the wall material, with an elastic modulus of 3.1-3.3 GPa, which is suitable for the high-speed dispersion shear force during the coating preparation stage. The core material is a compound of 80 wt% polyisoprene and 20 wt% benzotriazole. When microcracks occur in the coating, it is subjected to stress and breaks, filling the cracks and passivating the substrate at the same time. The modified toughening system is composed of modified polysulfide rubber grafted with POSS and hydroxyl-terminated perfluoropolyether in a mass ratio of 10:1-10:3. The hydroxyl-terminated groups can crosslink with epoxy groups, reducing the glass transition temperature of the system.
[0024] Example 1
[0025] Raw material by weight: 50 parts modified epoxy resin, 30 parts amino resin, 15 parts urea-formaldehyde resin, 10 parts modified polysulfide rubber, 1 part hydroxyl-terminated perfluoropolyether, 5 parts self-healing microcapsules, 8 parts double-layer modified glass flakes, 8 parts titanium dioxide, 3 parts kaolin, 0.5 parts dispersant BYK-2070, 0.6 parts leveling agent BYK-306, 0.2 parts defoamer BYK-A530, 0.8 parts drying agent potassium isooctanoate, and 15 parts solvent ethyl acetate.
[0026] Preparation of bilayer modified glass flakes: 200-mesh glass flakes were dried at 105℃ for 24h. 5g of the flakes were added to 50mL of ethanol-water solution (ethanol:water = 4:1) and stirred for 15min. Then, 700mL of 0.1mol / L KH550 ethanol solution was added and stirred at 80℃ for 4h. The flakes were then filtered, washed, and dried to obtain amino-grafted glass flakes. The obtained product was then added to 600mL of 0.05mol / L octadecyltrimethoxysilane ethanol solution and stirred at 75℃ for 3h. The flakes were then filtered, washed, and dried to obtain bilayer modified glass flakes with a grafting rate of 2% for the oriented groups.
[0027] Preparation of self-healing microcapsules: 10g of melamine, 25mL of 37% formaldehyde solution, and triethanolamine were added to adjust the pH to 8.5. The mixture was stirred at 70℃ until transparent to obtain a melamine-formaldehyde prepolymer. 20g of core material (80wt% polyisoprene + 20wt% benzotriazole), 2g of sodium dodecylbenzenesulfonate, and 100mL of deionized water were emulsified for 30min to obtain an emulsion. The prepolymer was added dropwise to the emulsion, the pH was adjusted to 4.5, and the mixture was stirred at 65℃ for 3h. After filtration, washing, and drying, modified melamine-formaldehyde wall material microcapsules were obtained with an elastic modulus of 3.1GPa and a particle size of 10-15μm.
[0028] Coating preparation: Modified epoxy resin, urea-formaldehyde resin, modified polysulfide rubber, and hydroxyl-terminated perfluoropolyether were stirred and mixed at 80°C for 2 hours. Amino resin was added and stirred at 60°C for 1 hour. The remaining raw materials were then added and dispersed at 1500 r / min for 1.5 hours to obtain the target coating. Test samples with a dry film thickness of 50 ± 5 μm were prepared by scraper and cured at 60°C for 3 days before testing.
[0029] Example 2
[0030] Raw material by weight: 53 parts modified epoxy resin, 33 parts amino resin, 16 parts urea-formaldehyde resin, 11 parts modified polysulfide rubber, 2 parts hydroxyl-terminated perfluoropolyether, 7.5 parts self-healing microcapsules, 9 parts double-layer modified glass flakes, 9 parts titanium dioxide, 4 parts kaolin, 0.75 parts dispersant BYK-2070, 0.7 parts leveling agent BYK-306, 0.3 parts defoamer BYK-A530, 0.9 parts drying agent potassium isooctanoate, and 17.5 parts solvent ethyl acetate.
[0031] Preparation of bilayer modified glass flakes: 200-mesh glass flakes were dried at 107℃ for 24.5 h. 5.3 g of the dried flakes were added to 53 mL of ethanol-water solution (ethanol:water = 4:1) and stirred for 17 min. Then, 725 mL of 0.125 mol / L KH550 ethanol solution was added, and the mixture was stirred at 82℃ for 4.25 h. The flakes were then filtered, washed, and dried to obtain amino-grafted glass flakes. The obtained product was then added to 625 mL of 0.075 mol / L octadecyltrimethoxysilane ethanol solution and stirred at 77℃ for 3.5 h. The flakes were then filtered, washed, and dried to obtain bilayer modified glass flakes with a grafting rate of 3%.
[0032] Preparation of self-healing microcapsules: 12.5g of melamine, 30mL of 37% formaldehyde solution, and triethanolamine were added to adjust the pH to 8.5. The mixture was stirred at 70℃ until transparent to obtain a melamine-formaldehyde prepolymer. 25g of core material (80wt% polyisoprene + 20wt% benzotriazole), 2.5g of sodium dodecylbenzenesulfonate, and 125mL of deionized water were emulsified for 30min to obtain an emulsion. The prepolymer was added dropwise to the emulsion, the pH was adjusted to 4.5, and the mixture was stirred at 65℃ for 3h. The mixture was filtered, washed, and dried to obtain modified melamine-formaldehyde wall material microcapsules with an elastic modulus of 3.2GPa and a particle size of 12-18μm.
[0033] Coating preparation: Modified epoxy resin, urea-formaldehyde resin, modified polysulfide rubber, and hydroxyl-terminated perfluoropolyether were stirred and mixed at 85℃ for 2.25h. Amino resin was added and stirred at 65℃ for 1.25h. The remaining raw materials were then added and dispersed at 1500r / min for 1.75h to obtain the target coating. Test samples with a dry film thickness of 50±5μm were prepared by scraper and cured at 60℃ for 3d before testing.
[0034] Example 3
[0035] Raw material by weight: 55 parts modified epoxy resin, 35 parts amino resin, 17 parts urea-formaldehyde resin, 12 parts modified polysulfide rubber, 3 parts hydroxyl-terminated perfluoropolyether, 10 parts self-healing microcapsules, 10 parts double-layer modified glass flakes, 10 parts titanium dioxide, 5 parts kaolin, 1.0 part dispersant BYK-2070, 0.8 parts leveling agent BYK-306, 0.4 parts defoamer BYK-A530, 1.0 part drying agent potassium isooctanoate, and 20 parts solvent ethyl acetate.
[0036] Preparation of bilayer modified glass flakes: 200-mesh glass flakes were dried at 110℃ for 25h. 5.5g of the dried flakes were added to 55mL of ethanol aqueous solution (ethanol:water = 4:1) and stirred for 20min. Then, 750mL of 0.15mol / L KH550 ethanol solution was added and stirred at 85℃ for 4.5h. The flakes were then filtered, washed, and dried to obtain amino-grafted glass flakes. The obtained product was then added to 650mL of 0.1mol / L octadecyltrimethoxysilane ethanol solution and stirred at 80℃ for 4h. The flakes were then filtered, washed, and dried to obtain bilayer modified glass flakes with a grafting rate of 4% for the oriented groups.
[0037] Preparation of self-healing microcapsules: 15g of melamine, 35mL of 37% formaldehyde solution, and triethanolamine were added to adjust the pH to 8.5. The mixture was stirred at 70℃ until transparent to obtain a melamine-formaldehyde prepolymer. 30g of core material (80wt% polyisoprene + 20wt% benzotriazole), 3g of sodium dodecylbenzenesulfonate, and 150mL of deionized water were emulsified for 30min to obtain an emulsion. The prepolymer was added dropwise to the emulsion, the pH was adjusted to 4.5, and the mixture was stirred at 65℃ for 3h. After filtration, washing, and drying, modified melamine-formaldehyde wall material microcapsules were obtained with an elastic modulus of 3.3GPa and a particle size of 15-20μm.
[0038] Coating preparation: Modified epoxy resin, urea-formaldehyde resin, modified polysulfide rubber, and hydroxyl-terminated perfluoropolyether were stirred and mixed at 90℃ for 2.5h. Amino resin was added and stirred at 70℃ for 1.5h. The remaining raw materials were then added and dispersed at 1500r / min for 2h to obtain the target coating. Test samples with a dry film thickness of 50±5μm were prepared by scraper and cured at 60℃ for 3d before testing.
[0039] Comparative Example 1 Raw material parts by weight: 55 parts bisphenol A epoxy resin E-51, 35 parts amino resin, 17 parts urea-formaldehyde resin, 12 parts unmodified polysulfide rubber, 10 parts ordinary KH550 modified glass flakes, 10 parts titanium dioxide, 5 parts kaolin, 1.0 part dispersant BYK-2070, 0.8 parts leveling agent BYK-306, 0.4 parts defoamer BYK-A530, 1.0 part drying agent potassium isooctanoate, and 20 parts solvent ethyl acetate.
[0040] Preparation of ordinary modified glass flakes: 200-mesh glass flakes were dried at 110℃ for 25h. 5.5g of the flakes were added to 55mL of ethanol aqueous solution (ethanol:water = 4:1) and stirred for 20min. Then, 750mL of 0.15mol / L KH550 ethanol solution was added and stirred at 85℃ for 4.5h. The flakes were then filtered, washed, and dried to obtain ordinary modified glass flakes without grafting of long alkyl oriented groups.
[0041] Coating preparation: Bisphenol A epoxy resin, urea-formaldehyde resin, and unmodified polysulfide rubber were stirred and mixed at 90℃ for 2.5h, amino resin was added and stirred at 70℃ for 1.5h, and the remaining raw materials were added. The mixture was dispersed at 1500r / min for 2h to obtain the control coating. Test samples with a dry film thickness of 50±5μm were prepared by scraping and cured at 60℃ for 3d before testing.
[0042] Comparative Example 2 (Conventional Self-Healing Coating Solution) Raw material parts by weight: 55 parts bisphenol A epoxy resin E-51, 35 parts amino resin, 17 parts urea-formaldehyde resin, 12 parts unmodified polysulfide rubber, 10 parts ordinary urea-formaldehyde wall material self-healing microcapsules, 10 parts ordinary KH550 modified glass flakes, 10 parts titanium dioxide, 5 parts kaolin, 1.0 part dispersant BYK-2070, 0.8 parts leveling agent BYK-306, 0.4 parts defoamer BYK-A530, 1.0 part drying agent potassium isooctanoate, and 20 parts solvent ethyl acetate.
[0043] Preparation of ordinary modified glass flakes: 200-mesh glass flakes were dried at 110℃ for 25h. 5.5g of the flakes were added to 55mL of ethanol aqueous solution (ethanol:water = 4:1) and stirred for 20min. Then, 750mL of 0.15mol / L KH550 ethanol solution was added and stirred at 85℃ for 4.5h. The flakes were then filtered, washed, and dried to obtain ordinary modified glass flakes without grafting of long alkyl oriented groups.
[0044] Preparation of self-healing microcapsules for ordinary urea-formaldehyde wall materials: 30g urea, 40mL 37% formaldehyde solution, and triethanolamine were added to adjust the pH to 8.0. The mixture was stirred at 70℃ until transparent to obtain a urea-formaldehyde prepolymer. 30g core material (100wt% polyisoprene), 3g sodium dodecylbenzenesulfonate, and 150mL deionized water were emulsified for 30min to obtain an emulsion. The prepolymer was added dropwise to the emulsion, the pH was adjusted to 3.5, and the mixture was stirred at 65℃ for 3h. After filtration, washing, and drying, ordinary urea-formaldehyde wall material microcapsules were obtained with an elastic modulus of 1.8GPa and a particle size of 15-20μm.
[0045] Coating preparation: Bisphenol A epoxy resin, urea-formaldehyde resin, and unmodified polysulfide rubber were stirred and mixed at 90℃ for 2.5h, amino resin was added and stirred at 70℃ for 1.5h, and the remaining raw materials were added. The mixture was dispersed at 1500r / min for 2h to obtain the control coating. Test samples with a dry film thickness of 50±5μm were prepared by scraping and cured at 60℃ for 3d before testing.
[0046] Table Test Data and Explanation Table 1 Comparison of core components in each experimental group
[0047] Explanation of the table: This table clearly presents the differences in the core components of each experimental group. Examples 1-3 include the component dosage ranges limited by technical requirements. The two comparative examples correspond to existing publicly available solutions and industry-standard self-healing coating solutions, respectively. There are no additional variables. The rigor of the control experiment meets the requirements of polymer coating testing standards.
[0048] Table 2 Performance test results for each experimental group
[0049] Note: All test methods refer to the national coating performance test standards. The self-healing efficiency is the ratio of the corrosion inhibition efficiency after scratching to the corrosion inhibition efficiency of the intact coating.
[0050] Explanation of the table: The data in this table show that Examples 1-3 have better corrosion inhibition efficiency, self-healing efficiency, and low-temperature impact resistance than the two comparative examples, verifying that the technical solution of this invention can effectively solve the three core defects of the prior art. Comparative Example 2 has a microcapsule breakage rate of 18.5%, verifying the defect of ordinary urea-formaldehyde wall material microcapsules being prone to premature failure; Comparative Example 1 has a self-healing efficiency of less than 15%, verifying the defect of the prior art lacking self-healing ability; the low-temperature impact resistance of the two comparative examples is only about 50% of that of the examples, verifying the defect of insufficient low-temperature toughness in the prior art.
[0051] refer to Figure 2 This figure visually presents the core performance differences between the three sets of embodiments and the two sets of prior art comparative examples. It can be clearly observed that the three core performance aspects of the technical solution of the present invention are superior to those of the two sets of comparative examples. This effectively solves the three core defects mentioned in the background technology: lack of self-healing function, low barrier efficiency, and poor low-temperature impact resistance. At the same time, the performance fluctuation of the three sets of embodiments is less than 2%, which verifies the product performance stability within the formulation parameter range of the present invention and provides intuitive and visual support for the component dosage range limited by technical requirements.
[0052] refer to Figure 3 This figure shows the trend of barrier performance changes of different sample coatings under strong corrosive environment. It can be clearly seen that the corrosive medium penetration rate of the coating of the present invention is only about 30% of that of the comparative example of the prior art. This verifies that the multi-level barrier network constructed by the directional arrangement of the double-layer modified glass flakes and the modified epoxy resin main chain effectively extends the penetration path of the corrosive medium and solves the defect of low barrier efficiency in strong corrosive environment of the prior art. At the same time, the penetration depth increases steadily under different immersion cycles, which verifies the reliability of the long-term corrosion resistance of the coating of the present invention and provides a visual reference for the prediction of the service life of the coating.
[0053] refer to Figure 4 This figure shows the difference in breakage rate between the two types of microcapsules under different high-speed dispersion shear forces. It can be clearly seen that the breakage rate of the microcapsules of the present invention is less than 1% in the commonly used rotation speed range of 1200-1800 r / min in coating preparation, which is lower than that of ordinary urea-formaldehyde wall material microcapsules. This verifies the design effect of adapting the elastic modulus of the wall material to the shear force of coating production, solves the defect of the existing self-healing microcapsules that are prone to premature breakage and failure in the preparation stage, provides visual support for the rationality of the microcapsule wall material parameters, and also reflects the process compatibility of the technical solution of the present invention with existing coating production lines.
[0054] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A novel high-weather-resistant resin coating, characterized in that, The raw materials include the following parts by weight: 45-55 parts rare earth-doped modified epoxy resin, 20-28 parts fluorine-modified hydroxyl acrylic resin, 25-32 parts amino resin, 8-12 parts fluorine-containing side-chain modified polysulfide rubber, 5-8 parts corrosion-inhibiting self-healing microcapsules, 7-10 parts titanium dioxide, 2-4 parts hydrophobic modified fumed silica, 0.4-1.0 parts dispersant, 0.5-0.8 parts leveling agent, 0.2-0.4 parts defoamer, 0.7-1.0 parts drying agent, and 12-20 parts solvent.
2. The novel high weather-resistant resin coating according to claim 1, characterized in that, The dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is cobalt isooctanoate, and the solvent is a mixture of propylene glycol methyl ether acetate and ethyl acetate in a volume ratio of 1:
1.
3. The novel high weather-resistant resin coating according to claim 1, characterized in that, The preparation of the rare earth-doped modified epoxy resin includes the following steps: S1. 1,10-Phenanthroline-2-carboxylic acid methyl ester and selenium dioxide were added to glacial acetic acid solvent, heated to 110-115℃ and stirred under reflux for 6-7 h, and then recrystallized with ethyl acetate after rotary evaporation under reduced pressure to obtain 9-keto-1,10-phenanthroline-2-carboxylic acid methyl ester intermediate. S2. Add cerium-doped glass flakes to a 95% (v / v) ethanol aqueous solution and stir for 15-20 min. Add an ethanol solution of KH550 silane coupling agent and heat to 80-85℃ and reflux for 4-4.5 h. After filtration, wash three times each with deionized water and ethanol and dry to obtain amino-modified cerium-doped glass flakes. S3. The intermediate methyl 9-keto-1,10-phenanthroline-2-carboxylic acid was added to a sodium hydroxide methanol solution and refluxed for 2 h. The pH was adjusted to acidic and a solid precipitated. After drying, it was added to dichloromethane, and the carbodiimide condensing agent EDC and the catalyst DMAP were added. The mixture was stirred and activated for 30 min. Then, amino-modified cerium-doped glass flakes were added. The mixture was stirred at room temperature for 24 h under nitrogen protection. After filtration and washing, amide-grafted 9-keto-diazonium-modified glass flakes were obtained. S4. Add 9-keto-fluorene-modified glass flakes, phenol, and zinc chloride to concentrated hydrochloric acid, heat to 45-50℃ and stir for 12-13 hours. The 9-keto group undergoes an electrophilic addition reaction with two molecules of phenol to obtain a bisphenol-terminated modified glass flake intermediate. Under nitrogen protection, mix bisphenol A, the bisphenol-terminated modified glass flake intermediate, epichlorohydrin, and tetrabutylammonium bromide, heat to 75-80℃ and stir for 3.5-4 hours. Add a 40%-45% sodium hydroxide solution and continue the reaction for 1-1.5 hours. After extraction, washing, drying, and vacuum distillation, obtain rare earth-doped modified epoxy resin.
4. The novel high weather-resistant resin coating according to claim 3, characterized in that, In step S2, the cerium doping mass fraction of the cerium-doped glass flakes is 2%-3%, the concentration of the ethanol solution of the silane coupling agent is 0.12-0.16 mol / L, and the ratio of cerium-doped glass flakes, ethanol aqueous solution, and silane coupling agent ethanol solution is 5-6 g: 50-60 mL: 720-760 mL; in step S4, the ratio of bisphenol A, bisphenol end-modified glass flake intermediate, and epichlorohydrin is 22-24 g: 4-4.2 g: 190-195 g.
5. The novel high weather-resistant resin coating according to claim 1, characterized in that, The preparation of the fluorinated side-chain modified polysulfide rubber includes the following steps: S1. Mix terminal mercapto-based liquid polysulfide rubber with 1,2-dichloroethane and stir until homogeneous. Add 0.5 mol / L sodium ethoxide ethanol solution dropwise, heat to 55-60℃ and stir for 3-3.5 h. After vacuum distillation, terminal chloride polysulfide rubber is obtained. S2. Under a nitrogen protective atmosphere, add the chlorinated polysulfide rubber to a mixed solvent obtained by mixing isopropanol and toluene at a volume ratio of 2:1, stir for 10-15 min, then add N-allyl perfluorooctyl sulfonamide, heat to 75-80℃ and stir for 4.5-5 h, cool and filter, and distill under reduced pressure to obtain the terminal alkenyl polysulfide rubber containing perfluorinated side chains. S3. Add terminal alkenyl polysulfide rubber containing perfluorinated side chains to dichloromethane and stir for 30-35 min. Add m-chloroperoxybenzoic acid and stir at room temperature for 8-9 h to oxidize the double bonds and obtain a fluorinated epoxy intermediate. S4. Add the fluorinated epoxy intermediate and aminopropylheptyl POSS to dimethyl sulfoxide, heat to 50-60℃ and stir for 24-25 hours, filter and dry to obtain fluorinated side chain modified polysulfide rubber.
6. The novel high weather-resistant resin coating according to claim 5, characterized in that, In step S2, the ratio of terminal chlorinated polysulfide rubber to N-allyl perfluorooctyl sulfonamide is 1 mol: 1.05 mol; in step S4, the ratio of fluorinated epoxy intermediate to aminopropylheptyl POSS is 8-9 g: 19-21 g.
7. The novel high weather-resistant resin coating according to claim 1, characterized in that, The wall material of the corrosion-inhibiting self-healing microcapsules is melamine-formaldehyde resin with a thickness of 1.2-1.5 μm, and the core material is a mixture of linseed oil and benzotriazole at a mass ratio of 7:
3. The microcapsules have a particle size of 15-25 μm, a shear strength of not less than 3000 rpm, and a temperature resistance of not less than 120℃.
8. The novel high weather-resistant resin coating according to claim 7, characterized in that, The preparation steps of the corrosion-inhibiting self-healing microcapsules are as follows: S1. Melamine and a 37% formaldehyde solution are mixed at a mass ratio of 1:
2. The pH is adjusted to 8-9, and the temperature is raised to 60-65℃ and stirred until the solution is clear to obtain melamine-formaldehyde prepolymer. S2 adds the core material to a 2% (w / w) aqueous solution of sodium dodecylbenzenesulfonate and emulsifies at high speed for 20-25 min to obtain a core material emulsion. The prepolymer is then slowly added dropwise to the core material emulsion at a mass ratio of 1:
2. The pH is adjusted to 4-5, and the mixture is heated to 70-75℃ and stirred for 3-3.5 h. After cooling, the mixture is filtered, washed, and dried to obtain corrosion-inhibiting self-healing microcapsules.
9. A method for preparing a novel high weather-resistant resin coating, used to prepare the novel high weather-resistant resin coating according to any one of claims 1 to 8, characterized in that, Includes the following steps: S1. Rare earth-doped modified epoxy resin, fluorinated side-chain modified polysulfide rubber, and fluorinated modified hydroxyl acrylic resin are stirred and mixed at 85-95℃ for 2-2.5h, and amino resin is added and stirred at 65-75℃ for 1-1.5h to obtain the base material. S2. Add titanium dioxide and hydrophobically modified fumed silica to the base material and disperse at high speed of 2800-3000 r / min for 20-25 min. Then add dispersant, leveling agent, defoamer, drying agent and solvent. Disperse ultrasonically at 300-400W power for 15-20 min and cool to 40-50℃. S3. Add the corrosion-inhibiting self-healing microcapsules to the dispersed material and stir at a low speed of 800-1000 r / min for 10-15 min to obtain a new type of high weather-resistant resin coating.
10. A novel high-weather-resistant resin coating according to claim 9, characterized in that, In step S2, the high-speed dispersion speed shall not exceed 3000 rpm, and in step S3, the temperature during the stirring process shall be controlled at 40-50℃.
Citation Information
Patent Citations
High-weather-resistant anticorrosive epoxy resin coating and preparation method thereof
CN119859455A